Detection of avoided crossings by fidelity - Plötz, Patrick; Lubasch, Michael; Wimberger, Sandro (Physica. A, Statistical mechanics and its applications, 2011)
The fidelity, defined as overlap of eigenstates of two slightly different Hamiltonians, is proposed as an efficient detector of avoided crossings in the energy spectrum. This new application of fidelity is motivated for model systems, and its value for analyzing complex quantum spectra is underlined by applying it to a random matrix model and a tilted Bose-Hubbard system.